Computation of business cycle models : a comparison of numerical methods - Burkhard Heer; Alfred Maußner (Center for Economic Studies and ifo Institute (CESifo), 2004)
We compare the numerical methods that are most widely applied in the computation of the standard business cycle model with flexible labor. The numerical techniques imply economically insignificant differences with regard to business cycle summary statistics except for the volatility of investment. Furthermore, these results are robust with regard to the choice of the functional form of the utility function and the model's parameterization. In conclusion, the simplest and fastest method, the log-linearization of the model around the steady state, is found to be most convenient and appropriate for the standard business cycle model.
Keywords: E32; C68; C63; 330; log-linearization; projection methods; extended path; value function iteration; parameterized expectations; genetic search; Konjunkturtheorie; Arbeitsmarktflexibilisierung; Numerisches Verfahren; Vergleich; Theorie